Environmental Derivatives, Risk Analysis, and Conservation Management. Issue 3 (26th June 2013) - Little, L. Richard; Parslow, John; Fay, Gavin; Grafton, R. Quentin; Smith, Anthony D.M.; Punt, André E.; Tuck, Geoffrey N.
Abstract Two key challenges in conservation management are: (1) how to quantify and manage the risk that natural populations will fall below critical thresholds and (2) how to fund recovery plans should a population do so. Statistically estimated, process‐based simulation models of two distinct fish populations are used to forecast the species population levels, and capture the risk of crossing a management defined trigger point. We show how to calculate the environmental derivative price, which is the amount a risk‐neutral investor would require for promising a pay‐out should the species abundance fall below the trigger level. The approach provides the potential for environmental derivatives to support species recovery, and a method for measuring the underlying "health" of a managed population and calculating risk‐cost tradeoffs among alternative management strategies.